Karakterisasi Morfologi Tanaman Manggis (Garcinia mangostana L.) Di Kabupaten Solok Selatan Sumatera Barat - Abimanyu Bagus Saputra1; Yora, Muharama; Renfiyeni; Afrahamiryano; Mahmud; Ahmad Imtaz Sumbari (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
South Solok Regency is one of the areas in West Sumatra that has quite high mangosteen production. Based on preliminary studies in the field, it can be seen that many people grow this plant, both in yards and gardens, which has quite a high diversity of morphological forms. The aim of this research is to explore mangosteen plants spread across South Solok Regency, as well as observe the characteristics of mangosteen plants, especially the vegetative parts of the plant. The sampling or accession technique was carried out randomly and deliberately. Cluster analysis was carried out with PBSTAT and displayed in the form of a dendogram. The results of cluster analysis of 111 plant accessions showed that there were 4 clusters of mangosteen plants which had characteristics and traits that dominated each cluster. The dissimilarity coefficient obtained ranges from 0.00 – 1.2. Cluster I consists of 26 accessions and Cluster II consists of 25 accessions with a dissimilarity coefficient value of 0.65, while Cluster III consists of 27 accessions and Cluster IV consists of 33 accessions with a dissimilarity coefficient value of 0.9. Keywords: Mangosteen (Garcinia mangostana .L), clusters, morphological characters